2020
DOI: 10.1007/s10198-020-01218-4
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of interventions aimed at major infectious disease threats: lessons from the literature

Abstract: Pandemics and major outbreaks have the potential to cause large health losses and major economic costs. To prioritize between preventive and responsive interventions, it is important to understand the costs and health losses interventions may prevent. We review the literature, investigating the type of studies performed, the costs and benefits included, and the methods employed against perceived major outbreak threats. We searched PubMed and SCOPUS for studies concerning the outbreaks of SARS in 2003, H5N1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…To our knowledge, this is the first study to estimate the total direct costs of secondary care of COVID‐19 associated with overweight and obesity in Europe. The lack of knowledge on costs of COVID‐19 is in line with previous studies, which found that there is generally little evidence on the cost of infectious diseases 30,31 . Because COVID‐19 is a novel disease, the knowledge regarding the disease is limited and the long‐term effects are unknown.…”
Section: Discussionsupporting
confidence: 70%
“…To our knowledge, this is the first study to estimate the total direct costs of secondary care of COVID‐19 associated with overweight and obesity in Europe. The lack of knowledge on costs of COVID‐19 is in line with previous studies, which found that there is generally little evidence on the cost of infectious diseases 30,31 . Because COVID‐19 is a novel disease, the knowledge regarding the disease is limited and the long‐term effects are unknown.…”
Section: Discussionsupporting
confidence: 70%
“…Its design drew on the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) statement and a previous review of the costs and benefits of interventions aimed at major infectious disease threats. 13,14 We extracted data for all costed activities; outcomes of interest included the scope and type of costed preparedness activities, the costing methods, estimated costs, and cost drivers. LC and EP independently extracted data for studies and then cross-validated the data extraction.…”
Section: Data Collectionmentioning
confidence: 99%
“…A study in South Africa has suggested that a combination of interventions could be cost-effective (US$ 340 per lifetime years of lives saved). However, it is difficult to generalize the findings because of the different resources, threats, and living environments ( 5 ).…”
Section: Introductionmentioning
confidence: 99%